2015
DOI: 10.1088/0004-637x/806/2/160
|View full text |Cite
|
Sign up to set email alerts
|

SN 2013ej: A TYPE IIL SUPERNOVA WITH WEAK SIGNS OF INTERACTION

Abstract: We present optical photometric and spectroscopic observations of supernova 2013ej. It is one of the brightest type II supernovae exploded in a nearby (∼ 10 Mpc) galaxy NGC 628. The light curve characteristics are similar to type II SNe, but with a relatively shorter (∼ 85 day) and steeper (∼ 1.7 mag (100 d) −1 in V ) plateau phase. The SN shows a large drop of 2.4 mag in V band brightness during plateau to nebular transition. The absolute ultraviolet (UV) light curves are identical to SN 2012aw, showing a simi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

18
103
2

Year Published

2015
2015
2019
2019

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(123 citation statements)
references
References 80 publications
(119 reference statements)
18
103
2
Order By: Relevance
“…Leonard et al (2013) also considered the alternative possibility that this feature is a separate high-velocity component of Hα; however, there is no comparable highvelocity feature associated with Hβ. Therefore, we favor the Si II identification, which is supported by the spectral modeling of Bose et al (2015) and Dhungana et al (2016) and is also the consensus among other studies of SN 2013ej in the literature (Valenti et al 2014;Huang et al 2015;Yuan et al 2016).…”
Section: Polarization Of Sn 2013ejsupporting
confidence: 83%
See 1 more Smart Citation
“…Leonard et al (2013) also considered the alternative possibility that this feature is a separate high-velocity component of Hα; however, there is no comparable highvelocity feature associated with Hβ. Therefore, we favor the Si II identification, which is supported by the spectral modeling of Bose et al (2015) and Dhungana et al (2016) and is also the consensus among other studies of SN 2013ej in the literature (Valenti et al 2014;Huang et al 2015;Yuan et al 2016).…”
Section: Polarization Of Sn 2013ejsupporting
confidence: 83%
“…The SN exhibited a peak absolute magnitude of~-17.5 and a nebular-phase decline rate consistent with a small mass of radioactive 56 Ni in the range 0.013-0.023 M e (Dhungana et al 2016;Yuan et al 2016). Although SN 2013ej was initially classified as an SN II-P (Leonard et al 2013;Valenti et al 2014), subsequent studies showed that the relatively fast decline rate during the recombination phase (∼1.2 mag in the first 50 days after rising up to the plateau; Valenti et al 2016) and some of the spectroscopic features appeared similar to those of SNe from the II-L class (Bose et al 2015;Huang et al 2015;Dhungana et al 2016;Valenti et al 2016). The distinction between SNII-L and II-P light curves is not always obvious (Anderson et al 2014;Sanders et al 2015); indeed, large samples have revealed a continuum of light-curve morphologies that are intermediate between sources classified as SNe II-P and SNe II-L.…”
Section: Introductionmentioning
confidence: 99%
“…Details of its early photometric and spectroscopic observations may be found in Valenti et al (2014), while for the analysis of the preexplosion image obtained with the Hubble Space Telescope (HST) see Fraser et al (2014). Originally classified as Type IIP, this SN was reclassified later as Type IIL, based on a fast (1.74 mag 100 days in V-band) decline rate of the luminosity as well as arelatively slow decline of the Hα and Hβ velocity profiles, which are characteristic for this subclass (see Faran et al 2014aFaran et al , 2014bBose et al 2015).…”
Section: Sn 2013ejmentioning
confidence: 99%
“…This could be a signal of possible asymmetry in the ejecta, or could arise due to scattering of the SN light by a dusty CSM(e.g., Wang & Wheeler 1996). SN 2013ej was previously modeled semi-analytically in the work of Bose et al (2015), where its ejecta mass, pre-explosion radius, and explosion energy were estimated to be M 12  , R 450  , and 2.3 10 erg 51 , respectively. Hydrodynamical simulations of Huang et al (2015) suggest an ejecta mass of M 10.6  , a pre-explosion radius of R 600  , and an explosion energy of 0.7 10 erg 51´f or this SN.…”
Section: Sn 2013ejmentioning
confidence: 99%
“…Another case in point is SN 2013ej: dubbed a "slow-rising" type II-P SN by Valenti et al (2014), while Bose et al (2015) favour a "Type II-L" classification based on its post-peak decline rate. We find it to be similar to the "fast-declining" SNe II-P in that it is relatively bright, and has a relatively long rise time compared to other SNe II-P (see Table 4).…”
Section: Rise Time Correlationsmentioning
confidence: 99%